2013
DOI: 10.1016/j.vaccine.2013.04.084
|View full text |Cite
|
Sign up to set email alerts
|

Influence of initial vaccination with 13-valent pneumococcal conjugate vaccine or 23-valent pneumococcal polysaccharide vaccine on anti-pneumococcal responses following subsequent pneumococcal vaccination in adults 50 years and older

Abstract: In adults 50 to 64 years of age, initial vaccination with PCV13 establishes an immune state that results in recall anti-pneumococcal responses upon subsequent vaccination with either conjugated or free polysaccharide vaccine. In contrast, initial vaccination with PPSV23 results in an immune state in which subsequent PPSV23 administration yields generally lower responses compared with the initial responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
119
1
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 17 publications
7
119
1
8
Order By: Relevance
“…For serotypes 3 and 14, the differences in responses between vaccines post vaccination were consistent with those observed in the current study. 12,13,27,41 As discussed above, a US study clearly demonstrated the ability to revaccinate PCV13 recipients with PCV13. 27 PCV13 was also shown to enhance responses to PPSV23.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…For serotypes 3 and 14, the differences in responses between vaccines post vaccination were consistent with those observed in the current study. 12,13,27,41 As discussed above, a US study clearly demonstrated the ability to revaccinate PCV13 recipients with PCV13. 27 PCV13 was also shown to enhance responses to PPSV23.…”
Section: Discussionmentioning
confidence: 82%
“…Some studies have observed that immune responses of some PPSV23 serotypes are significantly reduced upon revaccination at a 6-month to 4-year interval, which raises the question of hyporesponsiveness. [25][26][27][28][29] Other studies in the United States 30,31 and in Japan 32 demonstrated that when subjects were revaccinated with PPSV23 after an interval longer than 5 years, the serotypes studied were immunogenic when compared with prevaccination levels. Antibody responses on revaccination, although lower, were generally sustained when compared with those after the initial vaccination.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations